2006
DOI: 10.1029/2005gl024894
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric development of magnetospheric storms during magnetic clouds and sheath regions

Abstract: This study examines how the asymmetry in the low‐latitude geomagnetic field evolves during sheath and magnetic cloud domains of interplanetary coronal mass ejections using the Dst, SYMH and ASYH indices. For all investigated storms the station that contributed most to Dst was located in the dusk sector while the smallest disturbance field was concentrated around dawn. We found that sheath region storms are associated with larger morning/afternoon asymmetry than magnetic cloud storms. For sheath storms the stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
7
31
0
Order By: Relevance
“…Because of different occurrence rates of different solar wind streams it was found that 35% storms were generated by Ejecta with/without [Huttunen and Koskinen, 2004;Huttunen et al, 2006;Yermolaev et al, 2007aYermolaev et al, , b, c, 2010cPulkkinen et al, 2007a;Turner et al, 2009;Guo et al, 2011]. Our results confirm this conclusion.…”
Section: Discussionsupporting
confidence: 85%
“…Because of different occurrence rates of different solar wind streams it was found that 35% storms were generated by Ejecta with/without [Huttunen and Koskinen, 2004;Huttunen et al, 2006;Yermolaev et al, 2007aYermolaev et al, , b, c, 2010cPulkkinen et al, 2007a;Turner et al, 2009;Guo et al, 2011]. Our results confirm this conclusion.…”
Section: Discussionsupporting
confidence: 85%
“…for different drivers confirms high importance (Tsurutani et al, 1988;Tsurutani and Gonzalez, 1997) and high efficiency (Huttunen and Koskinen, 2004;Huttunen et al, 2006;Yermolaev et al, 2007a,b,c;Pulkkinen et al, 2007a;Turner et al, 2009) of Sheath in the generation of magnetic storms and indicates specific geoeffective conditions in Sheath. It is important to note that there are significant differences in parameters of MC and Ejecta (including their efficiencies), while differences in Sheath before MC and Sheath before Ejecta are not significant (Yermolaev et al, 2009(Yermolaev et al, , 2010b.…”
Section: Discussionmentioning
confidence: 65%
“…Because IMF lies in the ecliptic plane under steady interplanetary conditions and substantial B z < 0 is observed only in disturbed types of solar wind (SW), it was found in many investigations that interplanetary coronal mass ejections (ICME) and corotating interaction regions (CIR) are the most important drivers of magnetic disturbances on the Earth. Therefore, it is natural to categorize these solar wind drivers during a study of magnetic storm generation (see reviews and recent papers, for instance, Tsurutani et al, 1988;Tsurutani and Gonzalez, 1997;Gonzalez et al, 1999;Yermolaev and Yermolaev, 2002;Huttunen and Koskinen, 2004;Echer and Gonzalez , 2004;Denton et al, 2006;Huttunen et al, 2006;Yermolaev et al, 2007a,b,c;Pulkkinen et al, 2007a,b;Zhang et al, 2007;Turner et al, 2009;Yermolaev et al, 2010b, and references therein). As shown by numerous researchers, the different interplanetary drivers result in specific reactions of magnetosphere, for example, CIR-and ICME-induced magnetic storms (Huttunen et al, 2002;Pulkkinen et al, 2007a) or the specific development of substorms (Despirak et al, 2009).…”
mentioning
confidence: 99%
“…As has been shown by numerous papers, the dynamics of the magnetosphere during the development of magnetic storms significantly depends on the type of interplanetary driver (see, e.g., [Huttunen et al, 2002[Huttunen et al, , 2006Borovsky and Denton, 2006;Pulkkinen et al, 2007;Yermolaev et al, 2010Yermolaev et al, , 2012aGuo et al, 2011;Liemohn and Katus, 2012;Nikolaeva et al, 2013;Cramer et al, 2013] and references therein). These types of drivers are following: body of interplanetary CME (ICME) including magnetic cloud (MC) and Ejecta, and compression regions before high-speed solar wind stream (corotating interplanetary region -CIR) and before ICME (Sheath) (see, e.g., [Gosling, 1993;Gonzalez et al, 1999;Yermolaev et al, 2005]).…”
Section: Introductionmentioning
confidence: 99%